1992
DOI: 10.1002/hep.1840160210
|View full text |Cite
|
Sign up to set email alerts
|

The Hemodynamic Status of Preascitic Cirrhosis: An Evaluation Under Steady–State Conditions and After Postural Change

Abstract: To assess the hemodynamic status of patients with compensated cirrhosis, mean arterial pressure, cardiac index and peripheral vascular resistance and markers of central (plasma concentrations of atrial natriuretic factor) and arterial volemia (plasma norepinephrine concentration, plasma renin activity) were studied in 10 patients and 10 healthy control subjects under steady-state conditions (after 2 hr of standing) and after assumption of the supine position (30, 60, and 120 min). After standing, neither hemod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
48
0
5

Year Published

1994
1994
2005
2005

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(54 citation statements)
references
References 25 publications
1
48
0
5
Order By: Relevance
“…Such a prevalence was significantly higher than in the control group of patients with mild chronic hepatitis, in which it was comparable with that found in the general population. 27 Because Bazett' s formula can overestimate Q-T length at elevated heart rates, 31 the Q-T c prolongation seen in our patients could be due, at least in part, to their higher heart rates. However, this should not have substantially affected our results, because the prevalence of abnormal Q-T c did not significantly differ in patients with heart rate above or below 70 bpm, a rate beyond which Q-T c can be strongly influenced.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Such a prevalence was significantly higher than in the control group of patients with mild chronic hepatitis, in which it was comparable with that found in the general population. 27 Because Bazett' s formula can overestimate Q-T length at elevated heart rates, 31 the Q-T c prolongation seen in our patients could be due, at least in part, to their higher heart rates. However, this should not have substantially affected our results, because the prevalence of abnormal Q-T c did not significantly differ in patients with heart rate above or below 70 bpm, a rate beyond which Q-T c can be strongly influenced.…”
Section: Discussionmentioning
confidence: 79%
“…26,27 Plasma norepinephrine was evaluated by the modified extraction procedure according to Anton and Sayre 28 and high-pressure liquid chromatography with coulometric detection. The normal range for our laboratory is 100 to 400 pg/mL.…”
Section: Methodsmentioning
confidence: 99%
“…To evaluate whether the cardiac dysfunction in cirrhosis is influenced by canrenone, an aldosterone antagonist, 8 patients with preascitic, nonalcoholic cirrhosis, and portal hypertension underwent echocardiographic assessment of LV function and systemic hemodynamics and determinations of plasma volume, urinary sodium excretion, and plasma renin activity T he hemodynamic pattern of cirrhosis with portal hypertension, with high blood volume and cardiac output and low systemic vascular resistance (SVR), is thought to play a major role in the development of sodium retention and ascites. 1 Bernardi et al [2][3][4] showed that this hemodynamic pattern occurs only in the supine position; standing is associated with a reduction in cardiac output and an increase in SVR, that is, a "normalization" of systemic hemodynamics. This response to standing is quite different from that of healthy subjects, who do not show any appreciable changes in either cardiac output or SVR.…”
mentioning
confidence: 99%
“…1 Bernardi et al [2][3][4] showed that this hemodynamic pattern occurs only in the supine position; standing is associated with a reduction in cardiac output and an increase in SVR, that is, a "normalization" of systemic hemodynamics. This response to standing is quite different from that of healthy subjects, who do not show any appreciable changes in either cardiac output or SVR.…”
mentioning
confidence: 99%
See 1 more Smart Citation